"My business was not with lost souls and the underprivileged": The Contribution of Colin Badger (1906-1993) to Adult Education in Victoria, Australia - Peter Rushbrook (Adult Education Research Conference, 2001)
The paper is a narrative of the contribution of Colin Badger to Victorian adult education and the founding of the Council of Adult Education. Theoretical issues are raised about individual agency and historical change, and the place of narrative history in adult education research.